2018
DOI: 10.2140/apde.2018.11.133
|View full text |Cite
|
Sign up to set email alerts
|

Nodal geometry, heat diffusion and Brownian motion

Abstract: Abstract. We use tools from n-dimensional Brownian motion in conjunction with the Feynman-Kac formulation of heat diffusion to study nodal geometry on a compact Riemannian manifold M . On one hand we extend a theorem of Lieb (see [L]) and prove that any nodal domain Ω λ almost fully contains a ball of radius ∼, which is made precise by Theorem 1.6 below. This also gives a slight refinement of a result by Mangoubi, concerning the inradius of nodal domains ([Man2]). On the other hand, we also prove that no nodal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…We can now invoke the argument of Georgiev and Mukherjee [17] (their argument only uses that Brownian motion started in the point of maximum has a quantitatively controlled likelihood of hitting the boundary, which we have just established in the more general context): we present their argument in abbreviated form: if a large part of B were outside of , the likelihood of hitting the boundary would be large, but we just established that it is not.…”
Section: Proof Of Theorem 13mentioning
confidence: 95%
See 3 more Smart Citations
“…We can now invoke the argument of Georgiev and Mukherjee [17] (their argument only uses that Brownian motion started in the point of maximum has a quantitatively controlled likelihood of hitting the boundary, which we have just established in the more general context): we present their argument in abbreviated form: if a large part of B were outside of , the likelihood of hitting the boundary would be large, but we just established that it is not.…”
Section: Proof Of Theorem 13mentioning
confidence: 95%
“…Let n 3 and R n be open. Georgiev and Mukherjee [17] used this fact to refine Lieb's theorem. / 1=2 for which jB \ j .1 "/jBj: Little seems to be known about the location of the maximum.…”
Section: Higher Dimensionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In an influential work [28] Lieb showed that given any ε ∈ (0, 1) there exists r ε such that for any domain D ⊂ R d , with λ D being its Dirichlet principal eigenvalue in D for the Laplacian, it holds that |D ∩ B(x, r ε λ in several directions. For instance, [35] extends it for Schrödinger operators in R d , [14] establishes this on smooth Riemannian manifolds and [5] obtains an analogous version of this inequality for fractional Laplacian. In a similar direction we also cite [8,9] which studies Faber-Krahn type inequalities for the Schrödinger operators in R d involving singular potentials.…”
Section: Introductionmentioning
confidence: 87%